STRATEGI POSITIONING RADIO MANDIRI 98,3 FM SEBAGAI RADIO NEWS AND BUSINESS PEKANBARU - Geofakta Razali; Evawani Elysa Lubis (Universitas Bina Sarana Informatika, 2017)
Radio is a media which is heard by the whole society and used to support the development. To maintain the public space by creating a position in order to be accepted in society, radio needs to do a positioning radio strategy. Many radio has been expanding for the time, demanding a radio station must have a strong positioning to win a competition for gaining market segmentation which affect to sustainability of radio activity, one of them is advertisement. Mandiri FM radio as one of radio in Pekanbaru with tagline news and business radio trying to create a identity to be accepted by Pekanbaru citizen, with the concept of news and business to develope the Pekanbaru citizen’s who always require information such as news and business. This research aims to determine the positioning strategy of Mandiri FM as a news and business radio, and knowing the Mandiri FM constraints in performing the positioning strategy. This research uses a qualitative methods with a descriptive approach. The research was conducted at the Radio Mandiri FM, Tuanku Tambusai street, 7th Pekanbaru. With the research subject is positioning strategy Mandiri FM , and the object of research is all informant needs of this research, and for the key informants is Mandiri FM General Manager through purposive sampling . Techniques to collect the data for rthis research study is using depth observation, interviews and documentation. The results of this research show radio positioning (positioning) is a strategy to designed a communicate all of part of the radio beginning radio identity, segmentation, target, format and radio products (programs) and competitor analysis. The Tagline of Mandiri FM is news and business has a target audience segmentation is 25-35 year old and advertisers. To realize that segment needs for being the public space, Mandiri FM also presents the broadcast (program) that has been maintained by the format news and business.Keyword : Strategi, Strategi Positioning, Radio, News and Business